Emergency management in resolving an emergency situation - Irena Tušer; Šárka Hošková-Mayerová (Journal of Risk and Financial Management, 2020)
Experience gained from NATO operations shows that the basis for an effective solution to a crisis is a combination of a comprehensive political, civilian and military approach. The cooperation of all stakeholders is thus a basic prerequisite for the effective resolution of crisis situations. These aspects and stakeholders include emergency management. This paper deals with civil-military cooperation in times of emergency caused by the COVID-19 pandemic in the Czech Republic. It qualitatively evaluates the findings resulting from the questionnaire survey focused on the state of crisis preparedness of the Army of the Czech Republic and the functionality of emergency management in cooperation with rescue work with other teams of the rescue system. The questionnaire was carried out at military units in all regions of the Czech Republic; organizational units of the Ministry of Defence with nationwide competence, which were directly involved in securing measures related to the declaration of a state of emergency due to the COVID-19 pandemic in March-May, 2020; Operations Command, which currently manages operations in the Czech Republic designed to manage the consequences of a pandemic; and members of the Ministry of Defence participating in the activities of the Strategic Command and Control Group. A total of 21 stakeholders took part. The experience in managing the consequences of the COVID-19 pandemic have shown that armed forces around the world have an irreplaceable position in dealing with nonmilitary crises. The conclusions and recommendations obtained from the research survey are the content of this paper.
Keywords: 330; civilian-military cooperation; emergency management; emergency preparedness; rescue system; state of emergency; threats